Inquiring into academic timescapes - Vostal, Filip (Emerald Publishing Limited, 2021)
Proliferating literature claims that academia is in a critical condition, generating armies of anxious, neurotic and time-hungry individuals which are governed by the speed imperatives integral to a modernist and capitalist rationality. This book puts the temporal ordering of academic life under the microscope, and showcases the means of yielding a better understanding of how time and temporality act both as instruments of power and vulnerability within the academic space. This book brings together more than three dozen scholars who collectively craft a much-needed nuanced sociologically-driven perspective of temporalities in academia. Delving into contemporary processes which are quintessentially temporal in their character, such as the increasing precariousness of jobs among junior scholars, the prevalence of grant funding, the role of evaluation systems, and the political economy of higher education, the authors offer a forensic analysis of the complex nature of academic temporalities as experienced, understood, controlled, managed and contested in various academic and research contexts.